Effect of Diabetic Exercise on Reducing Cholesterol Levels in Type 2 Diabetes Mellitus Patients in the Prolanis Exercise Group Argasunya - Tifanny Gita Sesaria (Universitas Airlangga, 2022)
Introduction: Diabetes Mellitus (DM) or diabetes is a condition of disturbed metabolism in the body caused by the body's inability to produce and distribute the hormone insulin, causing instability in blood glucose levels. DM patients besides experiencing an increase in blood sugar levels also increase cholesterol levels caused by the body's inability to synthesize glucose into energy so that energy is formed from fat synthesis which can cause lipid deposits in the form of cholesterol. Management of diabetes mellitus (DM) which consists of diet, education, pharmacology and physical exercise. One of the physical exercise efforts is diabetes exercise, if done regularly it can burn 150 calories per day and is important in lowering plasma cholesterol through regulatory mechanisms.Method: This study aims to determine the effect of physical exercise on reducing cholesterol levels in patients with type 2 diabetes mellitus in the Prolanis Benowo Sukoharjo gymnastics group. This research is a quantitative study using a quasi-experimental design approachone group pretest-posttest. The sample in this study was patients with type 2 DMas many as 30 people, with statistical analysis using (paired sample t-test) withp-value (0.05).Results:The mean difference in cholesterol levels betweenpre andpost exercise in respondents who did gymnastics once a week for 4 weeks with a duration of 30 minutes per session was 35.8 with an SD of 34.7. While valuep (value) 0.000, meaning that there is a significant decrease in cholesterol levels betweenpre andpost physical exercise in respondents with type 2 diabetes mellitus. Conclusion:There is an effect of diabetes exercise on reducing cholesterol levels in patients with type 2 diabetes mellitus after being controlled with cholesterol medication in the prolanis exercise group.